The Relationship of Sports Participation in Academic Performance among College of Arts and Sciences Varsity Players - John Michael Aquino; Mary Grace Reyes (CV Rezki Media, 2022)
Background: Sports are featured in the curriculums of state universities and colleges (SUCs). The Laguna State Polytechnic University (LSPU) shines in sports competition throughout Region IV, and the College of Arts and Sciences (CAS) varsity athletes are actively engaging in this sports competition. Nevertheless, during the previous decade, the CAS had been routinely rated third to fifth in intramurals. Objectives: The researcher wish to ascertain the embodiment of CAS student athletes' experiences in sports involvement and academic performances to discover the significance of participation in sports and academic performance of students. The findings serve as the foundation for crafting Student Intervention Program. Methods: The descriptive survey approach was used to a total of 30 varsity players in CAS from the 5 programs. The Cronbach alpha was utilized to assess the overall consistency of the self-made instrument and was carried out to CAS students belong to the varsity team using an internet web service. Results: It was established that the student-athletes felt that all the assertions were evaluated as great in the university, especially in CAS, indicating satisfaction with the university's operations. Consequently, athletes excel in both athletics and academics. Conclusion: It was notably that CAS varsity players were deemed to be great by the student-athletes. Respondents were happy with the university's procedures as viewed and experienced in prior sports competitions held not just within the LSPU System but also at the Regional STRASUC or even National SCUAA. Students participating in sports are much more likely to excel academically.